Leadership style based on the study of multifactor leadership questionnaire in Palu Anutapura hospital - Fajrillah Kolomboy; Sukri Palutturi; Fridawaty Rifai; Lalu Muhammad Saleh; Nasrul; Ridwan Amiruddin (Gaceta Sanitaria, 2021)
Objective: Leadership style that can accommodate changes in uncertain times. The purpose of this study was to describe the leadership style of the head of the room in terms of the scale and construct of the Multifactor Leadership Questionnaire. Methods: This research was a descriptive type that was conducted at the Anutapura Hospital in August 2020. There were 22 treatment rooms and the researchers took all the heads of treatment rooms to be sampled. Collecting data using a Multifactor Leadership Questionnaire (MLQ-5X). Results: The results showed that 63.6% tend to use transformational leadership styles, 9.1% tend to use transactional leadership styles and 27.3% are based on the leader's outcomes. Conclusions: The dominant transformational leadership style used by the head of the room because it is considered effective in facing the era of globalization and modernization.